A Comparative Study of Suicide Cases in Pre-COVID and COVID Phases - Nath, Anamika; Thakuria, Pradip Kumar; Baruah, Aditya Madhab (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: India’s first case of COVID-19 was in January 2020. National lockdown brought along mental ailments like depression, anxiety, stress, phobias, etc. Objective: To find the number of suicidal deaths during the COVID pandemic and to compare the Pre-COVID phase, and the factors affecting them. Methods: This was a cross-sectional, retrospective study conducted at a tertiary care medical centre from 2018-2021. Suicide cases coming for autopsy in 2018-2019 and 2020-2021, excluding those where the manner of death was not documented, were analyzed. Age, sex, residence, occupation, and cause of death from Autopsy reports and Inquest papers were noted. Results: Out of 362 suicide cases, 43.64% were in Pre-COVID and56.35% in the COVID phase with 42.93% males in Pre-COVID and 57.70% in the COVID phase. Females were 52.06% in Pre-COVID and44% in the COVID phase. The majority of cases in the study period were in the 21-30 years and 31-40 years groups. Housewives were the majority in the Pre-COVID phase (32.91%), and daily-wage labourers in the COVID phase (49.26%). The number of hanging and burn cases were similar and the majority during the Pre-COVID phase, while in the COVID phase hanging cases were a majority. Conclusion: COVID-19 pandemic showed a rise in suicide cases and a shift towards male preponderance that was daily-wage labourers and hanging cases, which might be due to loss of pay during the phase. International Journal of Human and Health Sciences Vol. 07 No. 01 Jan’22 Page: 73-77